Family Caregiving for Individuals With Heart Failure: A Scientific Statement From the American Heart Association. Issue 22 (2nd June 2020) - Kitko, Lisa; McIlvennan, Colleen K.; Bidwell, Julie T.; Dionne-Odom, J. Nicholas; Dunlay, Shannon M.; Lewis, Lisa M.; Meadows, Ginny; Sattler, Elisabeth L.P.; Schulz, Richard; Strömberg, Anna
Abstract : Many individuals living with heart failure (HF) rely on unpaid support from their partners, family members, friends, or neighbors as caregivers to help manage their chronic disease. Given the advancements in treatments and devices for patients with HF, caregiving responsibilities have expanded in recent decades to include more intensive care for increasingly precarious patients with HF—tasks that would previously have been undertaken by healthcare professionals in clinical settings. The specific tasks of caregivers of patients with HF vary widely based on the patient's symptoms and comorbidities, the relationship between patient and caregiver, and the complexity of the treatment regimen. Effects of caregiving on the caregiver and patient range from physical and psychological to financial. Therefore, it is critically important to understand the needs of caregivers to support the increasingly complex medical care they provide to patients living with HF. This scientific statement synthesizes the evidence pertaining to caregiving of adult individuals with HF in order to (1) characterize the HF caregiving role and how it changes with illness trajectory; (2) describe the financial, health, and well-being implications of caregiving in HF; (3) evaluate HF caregiving interventions to support caregiver and patient outcomes; (4) summarize existing policies and resources that support HF caregivers; and (5) identify knowledge gaps and future directions for providers, investigators, health systems, and policymakers.